2016
DOI: 10.1093/aob/mcw110
|View full text |Cite
|
Sign up to set email alerts
|

Slow food: insect prey and chitin induce phytohormone accumulation and gene expression in carnivorousNepenthesplants

Abstract: The results suggest that upon insect prey catch a sequence of signals is initiated: (1) insect-derived chitin, (2) jasmonate as endogenous phytohormone signal, (3) the induction of digestive gene expression and (4) protein expression. This resembles a similar hierarchy of events as described from plant pathogen/herbivore interactions, supporting the idea that carnivory evolved from plant defences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Indeed, prey digestion gave rise to NH 4 + production in carnivorous plants (Scherzer et al, 2013). Another chemical agent that stimulates enzyme production is chitin, which probably acts through a LysM receptor kinase (Matu s ıkov a et al, 2005;Bemm et al, 2016;Yilamujiang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prey digestion gave rise to NH 4 + production in carnivorous plants (Scherzer et al, 2013). Another chemical agent that stimulates enzyme production is chitin, which probably acts through a LysM receptor kinase (Matu s ıkov a et al, 2005;Bemm et al, 2016;Yilamujiang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The application of chitin or ammonium salts activated the jasmonate signalling pathway and the expression of digestive enzymes probably through the LysM receptor or the depolarization of the membrane potential in digestive glands, respectively (Matu s ıkov a et al, 2005; Scherzer et al, 2013Scherzer et al, , 2015Libiakov a et al, 2014;Bemm et al, 2016;Jop c ık et al, 2017;Krausko et al, 2017). Chemical sensing is extremely important for inducing the carnivorous response through jasmonate signalling in passive Nepenthes pitcher traps, which are probably not able to generate electrical signals in response to prey capture (Buch et al, 2015;Yilamujiang et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%
“…The pitchers can detect enzymes in the pitcher fluids and respond accordingly to maintain an optimal cocktail of enzymes so that the benefits from prey digestion outweigh the costs of protein replenishment and pitcher metabolisms. Other studies also revealed that pitchers can regulate enzyme activities 24,46,58 . This is likely involving Ca 2+ and jasmonic acid (JA) signal transduction pathways 22 .…”
Section: Discussionmentioning
confidence: 94%
“…The findings that many proteases, chitinases, and glucanases found in the pitcher fluids can also be classified as PR proteins led to the inference that offensive carnivory mechanism evolved from existing plant defensive mechanism against herbivory 22 . This is also supported by the conserved jasmonate signalling of enzyme secretion during prey capture 23,24 .…”
mentioning
confidence: 81%
See 1 more Smart Citation